In Vitro Callus Induction in Tacca (Tacca chantrieri Andre) Leaf Explants on Murashige and Skoog Media with Different Concentrations of Sucrose - Isda, Mayta Novaliza; Salsabilla, Melda Jannatul (Universitas Andalas, 2022)
Tacca chantrieri belongs to the family Taccaceae has black flowers and has a long filiform that looks like a bat. T. chantrieri contains phytochemicals in the form of spritosol saponins used as traditional medicine by the people of China and Thailand. The amount of land clearing, forest exploitation and habitat destruction resulted in a reduction in the number of T. chantrieri, so T. chantrieri was propagated to maintain its sustainability. One way that can be used is the in vitro culture technique, namely callus culture. Callus culture is an early stage of in vitro culture technique where this stage aims to produce and multiply callus cells. The purpose of the study is were to determine the effect of different sucrose concentrations on callus induction from T. chantrieri leaf explants and determine the best sucrose concentrations for callus culture from T. chantrieri leaf explants on Murashige and Skoog (MS) media. This study used a single factor completely randomized design (CRD), namely sucrose concentrations 0 g/l, 10 g/l, 20 g/l, 30 g/l, 40 g/l, 50 g/l with five replications. The results of this study showed that the administrations of sucrose with different concentrations on MS media had an effect on increasing callus induction in Tacca chantrieri leaves. The best sucrose concertations for callus induction of Tacca chantrieri leaves was the addition of 40 g/l sucrose at 20 days after planting, 60 % callus formation percentage, callus formed in the form of compact callus and produce yellow-white callus.Â Keywords: Tacca chantrieri, sucrose, callus, Murashige and Skoog.